Age at type 1 diabetes onset does not influence attained brain volume - Tor-björn Claesson; Stefan Mutter; Jukka Putaala; Eero Salli; Daniel Gordin; Per-Henrik Groop; Juha Martola; Lena M. Thorn (BMC Endocrine Disorders)
Abstract Introduction Type 1 diabetes is suspected to hamper brain growth, implying that people with earlier diabetes onset would, on average, achieve lower maximal brain volume. We set out to test this hypothesis. Methods Examining brain MRI scans of middle-aged people with type 1 diabetes, we related age at diabetes onset to intracranial volume in 180 participants, as well as to cerebral gray and white matter volumes in a subset of 113 (63%) participants, using fractional polynomial regression models. Of the participants, 118 (67%) had been diagnosed with diabetes before 18 years of age. Results Of our participants, 54% were women, the median age 40.0 (IQR 33.2–45.0) years and the range of age at diabetes onset was 1.2–39.0 years. We found no association between age at diabetes onset and intracranial volume (p = 0.85), cerebral white (p = 0.10), or gray matter volumes (p = 0.12). Further, correlations between age at diabetes onset and the measured brain volumes were poor in analyses stratified for sex (all correlation coefficients ρ ≤ 0.16). Conclusions We found no association between age at diabetes onset and attained intracranial volume or gray or white matter volumes, indicating that type 1 diabetes may not have a clinically significant influence on brain growth.